2023
DOI: 10.4236/jhrss.2023.111008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of International Crude Oil Prices on Nigeria’s Gross Domestic Product from (1985-2020)

Abstract: The aim of this study is to investigate the effect of oil price and its volatility on the development of Nigeria's economy; this is due to the decline of the Nigerian economy as a result of decrease in daily oil production and plummeting oil prices. The study assesses both long-and short-term effects of oil price volatility on real GDP in Nigeria. To achieve the basic objective of this research and to ascertain a comprehensive and robust outcome, the study adopted secondary data such as Nigeria's Real GDP, Cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The demand and supply of oil depends on the internationally determined market price which can be affected by unpredictable global events (Nwosu, Anumudu, & Nnamchi, 2020). Thus, the price and production of crude oil remains an important component influencing the world's economic development, modern turn of events, food cost, poverty, and other financial factors, other than its elements is the primary list exhibiting oil market conditions (Jiménez-Rodríguez, 2008;Naranpanawa & Bandara, 2012;Sule-Iko & Nwoye, 2023). Crude oil in this study is believed to be the main driver of the economic condition of developing countries especially Africa continents Nigeria to be precise such that a rise in the price of crude oil significantly improves the country's revenue and a fall also affects the nation's revenue negatively (Sule-Iko & Ibrahim, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The demand and supply of oil depends on the internationally determined market price which can be affected by unpredictable global events (Nwosu, Anumudu, & Nnamchi, 2020). Thus, the price and production of crude oil remains an important component influencing the world's economic development, modern turn of events, food cost, poverty, and other financial factors, other than its elements is the primary list exhibiting oil market conditions (Jiménez-Rodríguez, 2008;Naranpanawa & Bandara, 2012;Sule-Iko & Nwoye, 2023). Crude oil in this study is believed to be the main driver of the economic condition of developing countries especially Africa continents Nigeria to be precise such that a rise in the price of crude oil significantly improves the country's revenue and a fall also affects the nation's revenue negatively (Sule-Iko & Ibrahim, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This indicates that certain money market instruments can affect price stability in Nigeria (Appah, 2023). The study by (2023) found that oil price volatility has a positive impact on real GDP in the short run, but its effect in the long run is not significant (Sule-Iko & Nwoye, 2023). This suggests that while oil price volatility can have a positive effect on economic development in the short term, it may not have a lasting impact (Sule-Iko & Nwoye, 2023).…”
Section: Introductionmentioning
confidence: 99%